2007
DOI: 10.1159/000104479
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hyperhomocysteinemia and Low Folate Concentrations as Risk Factors for Cervical Arterial Dissection

Abstract: Background and Purpose: Elevated homocysteine (Hcy) plasma levels are associated with an increased risk of spontaneous cervical artery dissection (sCAD). We examined the potential association between Hcy, folate, vitamin B12 levels and 5,10-methylenetetrahydrofolate reductase (MTHFR) polymorphisms in patients with cerebral infarct caused by sCAD. Patients and Methods: 39 patients who survived a cerebral infarct caused by sCAD [20 (51%) women; 24 (61.5%) vertebral and 15 (38.5%) internal carotid arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…Major and minor cervical trauma [13][14][15][16][17] Arterial hypertension [18][19][20] Young age 12 Current use of oral contraceptives 21 Migraine [22][23][24] Fibromuscular dysplasia 11,[25][26][27][28][29][30][31][32] Ultrastructural connective tissue abnormalities 33 Vascular subtype of Ehlers-Danlos syndrome 34 Marfan syndrome 18,35 Turner syndrome 19,36 Williams syndrome 37 Familial cases 18,38 Hereditary hemochromatosis 39 Osteogenesis imperfecta type I 40 α1-Antitrypsin deficiency 41,42 677T genotype MTHFR [43][44][45] Hyperhomocysteinemia 46 Cystic medial necrosis of intracranial vessels 47 Styloid process length 48 ICAM-1 E4690 K gene polymorphism 49 Autosomal-dominant polycystic kidney disease 50 Infections [51][52][53][54] Moyamoya disease …”
Section: Table 1 Factors Associated With CDmentioning
confidence: 99%
“…Major and minor cervical trauma [13][14][15][16][17] Arterial hypertension [18][19][20] Young age 12 Current use of oral contraceptives 21 Migraine [22][23][24] Fibromuscular dysplasia 11,[25][26][27][28][29][30][31][32] Ultrastructural connective tissue abnormalities 33 Vascular subtype of Ehlers-Danlos syndrome 34 Marfan syndrome 18,35 Turner syndrome 19,36 Williams syndrome 37 Familial cases 18,38 Hereditary hemochromatosis 39 Osteogenesis imperfecta type I 40 α1-Antitrypsin deficiency 41,42 677T genotype MTHFR [43][44][45] Hyperhomocysteinemia 46 Cystic medial necrosis of intracranial vessels 47 Styloid process length 48 ICAM-1 E4690 K gene polymorphism 49 Autosomal-dominant polycystic kidney disease 50 Infections [51][52][53][54] Moyamoya disease …”
Section: Table 1 Factors Associated With CDmentioning
confidence: 99%
“…51 Three studies found a positive association between the methylenetetrahydrofolate reductase (MTHFR) 677TT genotype and CAD. 8,9,66 Three other studies did not find any significant association between MTHFR 677TT and CAD. 7,13,60 We performed a meta-analysis of 5 studies 7,9,13,60,66 (in 440 cases and 1220 control subjects); the sixth study 8 was not included in the meta-analysis because of overlapping data with a subsequent analysis from the same group.…”
Section: Genetic Association Studiesmentioning
confidence: 89%
“…Five studies reported associations with 3 different candidate genes: ICAM-1, COL3A1, and MTHFR. 8,9,12,51,66 The associations with the ICAM-1 E469K polymorphism and the COL3A1 3ЈUTR 2-bp deletion, 12,51 observed in 2 relatively small studies, have not been replicated and should therefore be interpreted with caution. The ICAM-1 E469K polymorphism could modify the affinity of ICAM-1 to its ligands, which may lead to increased activation of cytokines and proteases, thus inducing extracellular matrix degradation and weakening of the arterial wall.…”
Section: Genetic Association Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of case-control studies evaluating the association between the MTHFR/C677T and carotid dissection [20,21,22,23]. Many of these reports have provided conflicting results often hampered by the relatively small number of subjects included in each study.…”
Section: Introductionmentioning
confidence: 99%